Clinical practice guidelines for dental management prior to radiation for head and neck cancer. (December 2021) - Watson, Erin; Dorna Mojdami, Zahra; Oladega, Afisu; Hope, Andrew; Glogauer, Michael
Highlights: Clinical practice guidelines for dental management prior to head and neck radiation. Guidelines developed based on expert consensus from dental oncologists. Radiation dose, patient factors, dental condition and tooth location considered. Frequently recommended for removal: periodontally involved teeth, mandibular molars. Symptomatic third molars recommended for removal if adequate healing time. Abstract: Purpose: Limited evidence exists linking the specific preventative dental care provided prior to radiation therapy (RT) for head and neck cancer to outcomes like osteoradionecrosis (ORN). This study utilized expert consensus to develop tooth-specific dental treatment pathways for head and neck cancer patients prior to radiation. Materials and Methods: Dental oncologists from across a single nation were engaged in a Modified Delphi process. Three rounds of questionnaires were performed followed by an in-person meeting. Domains included radiation dose, timing of dental treatment, and treatment of dental caries, periodontal disease and third molars. Results: The response rate from the 32 participants between rounds was > 70%. Consensus was reached for all but 4 questions. The radiation dose at which participants would prophylactically remove teeth to prevent ORN was established as 70 Gy in the maxilla and 60 Gy in the mandible. Treatment pathways were developed for maxillary and mandibular anterior/premolar and molar teeth receiving a dose at or above this threshold. Risk factors were established for carious, periodontally involved and third molar teeth. In general, periodontally involved teeth and mandibular molars were most frequently recommended for extraction. Only symptomatic third molars were recommended for extraction when adequate healing time was available prior to commencement of RT. Conclusion: Tooth-level clinical practice guidelines were developed using expert consensus via the modified Delphi process. The treatment pathways developed in this study will be prospectively tested to evaluate the outcomes associated with tooth-specific dental treatments.